A Literature Perspective of Key Factors Influencing Creativity and Conceptual Model for Virtual Learning Team Work - Setkhumbong, Thepphayaphong; Na-Songkhla, Jaitip; Tantrarungroj, Pornsook (Humanities, Arts and Social Sciences Studies, 2020)
Creativity is one of the values and sustainable skills that is often included as a learning objective in the context of online higher education. This competency enables learners to survive in the complex world we live in and to adapt to new settings and circumstances. Educational institutions, therefore, play a pivotal role in the development of essential cognition of learners, including the development of creative skills sets. However, identifying the best method of promoting and developing creativity among learners is a challenge for practitioner-educators. This paper provides a framework for educators to use in overcoming the challenge of creating effective teams that promote creative thinking in virtual environments. The key factors influencing virtual team creativity were explored by searching for research articles from five electronic databases: Scopus, ScienceDirect, ProQuest Dissertations & Theses Global, SpringerLink, and ResearchGate published from 2000-2017. Twenty-one research articles that relate to the key factors influencing virtual team creativity and to the objective of this study were analyzed and synthesized. The researchers propose six perspectives that provide a framework that can guide educators to foster creativity among learners in virtual team environments: Inter-Peer Trust and Attitude, Team Background and Size, Participation and Communication, Objectives, Leadership and Roles, and Experiential Factor. The study employed nine experts’ reliability examination methods, including three creativity experts, three virtual world experts, and three instructional experts, using a semi-structured interview.